Barriers and preferences to antenatal exercise among pregnant women in Kuala Selangor - Md Yunus, Nur Farhana; Abdul Manaf, Rosliza; Shahar, Hayati Kadir; Ismail, Suriani; Jathin, Romizan (Universiti Putra Malaysia Press, 2024)
Introduction: Physical activity during pregnancy offers numerous benefits for maternal and fetal health. However, the level of physical exercise is low among pregnant women worldwide. Physical inactivity and sedentary lifestyles among pregnant women significantly increase maternal health problems. This study aimed to determine the barriers and preferences to practice antenatal exercise (ANE) among women during pregnancy. Materials and methods: It was a cross-sectional study that included 553 pregnant women who attended antenatal follow-up at the government’s primary health clinics in Kuala Selangor. Data were collected from December 2021 to March 2022. A self-administered questionnaire was used that included socio-demographic information, barriers, and preferences to practice ANE. The collected data were analyzed using SPSS version 27. Results: The findings of this study showed that lack of information (n=346), tiredness (n=323), and lack of time (n=272) were three common barriers. Most participants preferred healthcare providers to provide ANE information and advice and a short video of antenatal exercise as the mode of delivery. Majority of them chose that exercise may ease labour (43.8%) as their main reason for exercising and preferred individual online exercise (45.4%) during pandemic era whereas physical group exercise (61.3%) during non-pandemic era. Conclusion: It is advised that an intervention be used to overcome each barrier found. To encourage pregnant women to be more active throughout pregnancy, healthcare professionals should receive training and be given the authority to serve as change agents.